The Effect of Implementing Strategy Management on Improving The Quality of Education of Madrasah Aliyah Negeri 1 North Bengkulu - Yanthy Herawati,; Ramadhan, Heldy; Rudi Hartono, (Technium Social Sciences Journal, 2020)
The purpose of this research, namely: (1) To find out the management of strategies in Madrasah Aliyah Negeri 1 North Bengkulu Regency (2) To know the improvement of the quality of education in Madrasah Aliyah State 1 North Bengkulu District (3) To know the effect of implementing strategy management on improving the quality of education in Madrasah Aliyah State 1 North Bengkulu District Sample in this study is the entire number of educators and educational personnel namely 30 people, and the sample used by researchers is "saturated sample". The data analysis techniques used are descriptive statistical analysis and inference statistical analysis using simple regression. The results of the descriptive statistical analysis showed strategy management was in the moderate category with a percentage of 66.67%, and the improvement in the quality of education was in the moderate category of 53.67%. The results of the inference statistical analysis show the value thitung = 2,968 ? ttabel = 2,048, then HO is rejected. Based on these results, it can be concluded that strategy management has an effect on improving the quality of education in Madrasah Aliyah Negeri 1 North Bengkulu Regency. With the implementation of effective and efficient strategy management will affect the quality of education so as to produce maximum school quality and in accordance with customer expectations